Seventy Years of Exploration in Oceanography A Prolonged Weekend Discussion with Walter Munk - Hasselmann, Klaus. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
The present volume documents an interview with the eminent oceanographer and geophysicist Walter Munk, who is one of the "grand old men" of oceanography. The book covers many key issues, such as ocean-wave prediction, ocean acoustic thermography. As a highly prominent scientist who has influenced many present day key oceanographers, Munk's career covers 70 years of practice, beginning about 1940 and continuing to the present.